Cancer Aetiology and Progression - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Genomic and metabolic profiles of cancer cells differ significantly from normal cells. Cancer cells utilise nutrients with an impaired metabolic process to maintain their high metabolic demands to adapt and proliferate. Metabolic rewiring in cancer cells has profound effects on the regulation of gene expression and vice versa. Genomic and metabolomic interactions are highly intertwined in both normal and cancer cells. Genomic components affect the metabolomic activities by modulating the expression of genes that regulate the metabolome. Inversely the metabolome, in turn, coordinates and provide a favourable microenvironment for genomic expression of metabolome regulating enzymes. The review aims to understand the link between genomic and metabolomic processes, their point of interaction, shared process, including dependent and independent networks in understanding cancer aetiology and progression. We systematically searched PubMed, Hinari, Google scholar and Nature journals to identify potentially relevant articles. We included reports that met the following criteria: (1) current knowledge on the cause of cancer as explained by genetic mutation, and (2) examine to what extent the mutation is determined by the metabolome. We also reviewed epigenetic aberration as hallmark of cancer aetiology. We discussed that the interaction between the genomic and metabolomic components is indispensable for the normal metabolic processes. Anything that alters the interplay of these processes will definitely cause impairment in the interaction and overall compromise in the entire genomic, metabolic, and cellular processes. Understanding the complex interaction between genome, epigenome, and metabolome is crucial to gain a greater insight into unravelling cancer pathogenesis and in the onset and progression of cancers and the potential of designing novel therapeutic strategies.